Eccrine Nevus Presenting with Umbilical Discharge: A Case Report and Review of the Literature. (21st March 2017) - Bidari-Zerehpoosh, Farahnaz; Sabeti, Shahram; Arman, Farid; Shakeri, Hania
Abstract : Eccrine nevus is a rare skin lesion with protean manifestations like hyperhidrosis, discolored nodules, papules, and so forth, which has been reported in various anatomic parts of the body including the forearm, leg, thigh, back, and coccyx. Our patient was a 26-year-old male, who presented with increasing colorless and odorless episodic umbilical discharge. First impression for the patient was an umbilical sinus and the patient underwent surgery. Histopathological study revealed the lesion to be an eccrine nevus of the umbilicus. This is the first case of eccrine nevus presenting with umbilical discharge. We recommend that eccrine nevus should be considered as a differential diagnosis for umbilical discharge.